The Influence of Sex Hormones on Cardiovascular Health: Current Perspectives and Future Directions - Eskandar, Kirolos (2024)
The intricate relationship between sex hormones and cardiovascular health has garnered increasing attention, revealing significant implications for both disease prevention and therapeutic strategies. This literature review aims to elucidate the multifaceted roles of estrogen, progesterone, and testosterone in cardiovascular physiology and pathology. Estrogen is widely recognized for its protective effects on vascular function, lipid metabolism, and atherosclerosis prevention, while testosterone presents a more complex picture with both beneficial and detrimental impacts on cardiovascular risk. Progesterone, often overlooked, also plays a critical role in modulating these effects. Additionally, this review explores how sex hormones influence endothelial function, inflammatory responses, and contribute to gender differences in cardiovascular disease prevalence. The impact of menopause and hormone replacement therapy (HRT) on cardiovascular health is critically examined, highlighting ongoing debates and current guidelines. Furthermore, the cardiovascular implications of gender-affirming hormone therapy in transgender individuals are discussed. By synthesizing current perspectives and identifying future research directions, this review underscores the potential for personalized medicine approaches that consider hormonal status to optimize cardiovascular health outcomes.